Influence of large strain preloads on the viscoelastic response of rubber-like materials under small oscillations. (May 2016) - Lectez, A.-S.; Verron, E.
Abstract: The viscoelastic response predicted by linearized internal variables models in the case of small oscillations superimposed on a large static preload is investigated, comparing simple forms of the Zener and the Poynting–Thomson models. It is shown that both of them predict a preload dependency of the equilibrium linearized stress, but only the latter take into account such a dependency on the out-of-equilibrium part. Yet, the Zener model is much more frequently linearized as the Poynting–Thomson model. The formulation of each model for finite deformations is quickly reminded, before linearizing them around a large static preload. Finally, a comparison of the influence of preload on each model is proposed for uniaxial extension, before discussing which kind of model has to be chosen regarding theoretical and practical aspects. Abstract : Highlights: Linearized viscoelastic models around a large static preload are investigated. Ability to predict an influence of preload on linearized overstress is highlighted. Zener-like models are mostly used and yet do not naturally predict this influence. Linearization of Poynting-Thomson model is original and predict such an influence.